The effect of financial liberalization on Chinese banking system - Chen, Wenting (2009)
Thought analysis how the effect on financial liberalization in literature view and in Practice in some counties, this paper tries to explore and develop a comprehensive picture by economic and literature view and a survey from domestic banks, foreign banks and Chinese banks’ regulatory to find that: how is the current situation for the Chinese banking system and who will take more risk under Chinese liberalization; What are the weakness and benefits of domestic and foreign banks. How could different strategies help Chinese banking system positioning them for the future, based on changes in this market structure, increased competition and future development? This research lies in the existing and increasing market competition for new and active exist banks after financial liberalization, which has affected Chinese domestic banks and regulators in a significant change and substantial challenge to Chinese banks. The various reforms that Chinese banks also are onerous in the extreme. This research is aim to find some suggestions and provide some reflections for banks in China during the financial liberalization transition or the processing of other developing countries.